THE MEASUREMENT OF PHYSICAL ABILITY EARLY AGE CHILDREN BY ADOPTING JAPANESE INSTRUMENTS IN KLATEN - Murni Ramli; Yudianto Sujana; Dyah Yuni Kurniawati; Nurul Kusuma Dewi; Mida Septi Karunia; Tri Ulya Wardati Qariah (Universitas Muhammadiyah Ponorogo, 2018)
The Curriculum 2013 entailed the importance of developing the physical ability (PA) of early age children (EAC). In fact, the standard measurement or instrument to assess the PA of early childhood has not been formulated yet to be used in the whole country. Therefore, it is required to develop the standard instrument to measure the physical ability of children. The Center for Japanese Studies, Research and Community Services of Universitas Sebelas Maret, Indonesia collaboratively worked with HIMPAUDI (The Association of Early Childhood Education Indonesia) of District Karanganom in Klaten Regency to develop the standard achievement of Klaten's children based on the instrument of PA adopted from Japan. This program involved 21 ECE nurseries in Karanganom, and 70 instructors participated in the program. The activities were based on an action research aimed to change the mindset of related instructors on PA, connection between PA and cognitive development. It also trained the skills of instructors on measuring the PA. The program was conducted from July to September 2017. As the program ran, data of children' PA was also measured, and as the entry of database developed for Karanganom. There are five indicators of PA which represent the stability, locomotive, and manipulative movements, adapted from Japanese PA measurement. The results of database showed the average measurement of children' PA in Karanganom, and were compared to the Japanese peers, the achievement was lower. The instrument has to be validated and examined in the various regions and periods.